Evaluation of Solid State Fermetation by Aspergillus Niger to Improve the Nutritive Value of Palm Kernel Cake for Broilers - Khin, Hnin Swe (2004)
A study was conducted to examine the effects of solid-state fermentation (SSF) by Aspergillus niger on the nutrient contents of palm kernel cake (PKC). The effects of different types and levels of alcohols were investigated on the enzyme activity and nutrient contents of fermented PKC+ rice bran (RB). The results showed that the neutral detergent fibre (NDF) and acid detergent fibre (ADF) contents of fermented substrate (FS) (PKC+RB) were decreased by 47.3% and 22.6% respectively, while the crude protein (CP) was increased by 28.7% after 8 days of fermentation and the activity of mannanase was 109.7 U/g at 6 days of fermentation. There were no significant effects (P>0.05) of ethanol and methanol on the nutrient contents and citric acid production in the fermented substrate. An experiment was conducted to improve the fermentation process of A. niger on PKC. Rice bran was added to PKC in varying proportions. Three different proportions of rice bran (lo%, 20% and 30% of total substrate) were used and the fermentation was carried out for 8 days. The results showed that the nutrient contents of FS were not significantly (P>0.05) affected by the RB added. Nevertheless, among the different substrate groups used, 70% PKC+ 30% RB showed the lowest concentration of ochratoxin (43.3ppb). The ochratoxin level of 100% PKC substrate group was 49.8 ppb. Therefore, based on the ochratoxin level, the substrate group consisting of 70% PKC + 30% RB was used as the substrate for SSF. The fermented substrate was used as an ingredient in the broiler ration. Four experimental diets were used in the feeding trial. They were: 1) control diet (without PKC), 2) diet containing 20% PKC, 3) diet containing 20% FS and 4) diet containing 25% FS. A total of 60 birds, 15 birds per treatment, 3 weeks old Arbor Acre were used. The birds were placed in individual cages. The growth trial was continued up to 42 days. The results showed poor (Pc0.05) growth performances of birds fed diets containing FS and the best performance was recorded in birds fed control diet. There were no significant (P>0.05) differences in the performance of birds fed diet containing 20% PKC and those fed control diet. Cumulative FCR of birds fed control diet was 1.85 whereas that of birds fed dietary treatment 4 was 2.42. The study on histopathological examination of visceral organs of chickens fed diet containing FS showed some lesions of ochratoxicosis where the immune organ (bursa of Fabricius) was adversely affected. The lesions in liver were less than those of the kidney. An attempt was carried out to delay sporulation of hngal culture. In this study, 14% ammonium sulphate was observed as the best concentration to add in culture during SSF of substrate (PKC+RB) by A. niger to delay sporulation. The digestibility of fibre was improved by adding ammonium sulphate in the culture. Although the nutritive value of fermented PKC was enhanced by SSF with A. niger, the feeding trial carried out in broilers showed no beneficial effect of using the fermented substrate as a ration component in poultry feed. Nevertheless, the information obtained in this study would be beneficial in the understanding of the biochemical changes that occur in PKC during SSF with A. niger.